Личностные детерминанты успешности профессиональной деятельности работников подразделений по чрезвычайным ситуациям - Greben', Н. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2011)
The results of psychological research, obtained by the method of expert estimation, in the field of personal determinants of successful professional activity of emergency units are presented. The detailed qualitative and quantitative analysis of results of the poll among 64 persons is given. The further prospects of study and practical use of revealed factors of successful activity of a rescuer are outlined.